Burden of healthcare-associated infections in Italy: incidence, attributable mortality and disability-adjusted life years (DALYs) from a nationwide study, 2016. (July 2021) - Bordino, V.; Vicentini, C.; D'Ambrosio, A.; Quattrocolo, F.; Zotti, C.M.; ,; Novati, R.; Sticchi, C.; Bersani, M.; Fedeli, U.; Fabbri, L.; Brusaferro, S.; et al.
Summary: Background: Healthcare-associated infections (HAIs) are an increasing public health threat. Measuring disease burden in disability-adjusted life-years (DALYs) allows the combination of morbidity and mortality into one figure, as it represents the summation of years lived with disability and years of life lost. Aim: To evaluate the incidence, attributable deaths and burden of the most significant HAIs in Italy. Methods: Prevalence data from the study sample of the 2016 national Point Prevalence Survey of HAIs in acute-care settings were used to estimate the incidence of five HAIs. The methodology from the Burden of Communicable Diseases in Europe (BCoDE)-project was employed for DALY calculations, adapting the disease models to the Italian population. Findings: We estimated a total of 641, 065 (95% uncertainty interval, UI 585, 543.00–699, 207.90) new yearly cases of HAIs and 29, 375 (95% UI 23, 705.97–35, 905.80) deaths in Italy in 2016. The total annual DALYs were estimated to be 424, 657.45 (95% UI 346, 240.35–513, 357.28), corresponding to 702.53 DALYs (95% UI 575.22–844.66) per 100, 000 general population. Bloodstream infections accounted for the majority of total DALYs (59%), healthcare-associated pneumonia for 29%, surgical site infections for 9%, CDI for 2% and urinary tract infections accounted for less than 1% of total DALYs. Conclusion: Results of this study suggest HAIs have a substantial burden in Italy. Reducing the burden of HAIs through infection prevention and control efforts is an achievable goal. This study provides data that could be used to guide policy-makers in the implementation of these measures.